Case report of novel CACNA1A gene mutation causing episodic ataxia type 2. (6th May 2017) - Isaacs, David Alan; Bradshaw, Michael J; Brown, Kelly; Hedera, Peter
Background: Episodic ataxia type 2 (OMIM 108500) is an autosomal dominant channelopathy characterized by paroxysms of ataxia, vertigo, nausea, and other neurologic symptoms. More than 50 mutations of the CACNA1A gene have been discovered in families with episodic ataxia type 2, although 30%–50% of all patients with typical episodic ataxia type 2 phenotype have no detectable mutation of the CACNA1A gene. Case: A 46-year-old Caucasian man, with a long history of bouts of imbalance, vertigo, and nausea, presented to our hospital with 2 weeks of ataxia and headache. Subsequent evaluation revealed a novel mutation in the CACNA1A gene: c.1364 G > A Arg455Gln. Acetazolamide was initiated with symptomatic improvement. Conclusion: This case report expands the list of known CACNA1A mutations associated with episodic ataxia type 2.